A scoping review critically examining research connecting social and emotional learning with three model-based practices in physical education: Have we been doing this all along?. (February 2021) - Dyson, Ben; Howley, Donal; Wright, Paul M.
The purpose of this scoping review is to critically examine previous research that connects three selected model-based practices (MBPs) to social and emotional learning (SEL) outcomes in K-12 physical education (PE) settings to inform a future research agenda for the field. A methodological framework involving the processes of inductive analysis and constant comparison was followed. Sixty-three studies (teaching personal and social responsibility = 26; cooperative learning = 24; and outdoor and/or adventure education = 13) across 14 countries adopting qualitative (26), quantitative (23), and mixed methods (14) in elementary (17), middle (27), and high school (19) settings presented evidence connecting these three MBPs explicitly, but more often implicitly, with SEL outcomes. While it is possible to say SEL skills and outcomes were observed, it would be more appropriate to suggest that there is evidence of only some key skills and elements of SEL outcomes occurring. Similar to general education, we do not know as much about if and how these three MBPs deliver such outcomes comprehensively. The educational and political rhetoric surrounding SEL is not matched by a body of empirical research that dedicates itself solely to investigating SEL in PE using a contemporary theory, framework, and assessment. Aligning future research involving these three MBPs and other pedagogical approaches with a suitable framework and theory involving teachers and students can advance future research on SEL in PE and is necessary in order to develop a common language and understanding within the field.